Pengaruh Kepemimpinan Transformasional, Growth Mindset dan Professional Growth terhadap Motivasi Kerja Guru SMAN Wilayah Hilir Kapuas: The Influence of Transformational Leadership, Growth Mindset, and Professional Growth on the Work Motivation of Teachers at State Senior High Schools (SMAN) in the Hilir Kapuas Region - Widy Noviani; Ahmad Suriansyah; Ngadimun Ngadimun (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Education is a strategic instrument in nation-building that relies heavily on teacher quality. Teacher work motivation is a crucial factor in fostering high-quality learning, particularly during the implementation of the Kurikulum Merdeka (Independent Curriculum). This study aims to analyse the direct and indirect effects of a school principal's transformational leadership on teacher work motivation, mediated by growth mindset and professional growth. A quantitative approach utilising path analysis was employed. The study population consisted of 271 public high school teachers in the downstream region of Kapuas Regency, with a sample of 162 respondents selected via simple random sampling. Data were collected using a five-point Likert scale questionnaire—validated for reliability and validity—and subsequently analysed using linear regression, path analysis, and the Sobel test. The results indicate that transformational leadership, growth mindset, professional growth, and teacher work motivation all fall within the high category. Transformational leadership exerts a positive and significant influence on work motivation, growth mindset, and professional growth. Furthermore, growth mindset and professional growth positively and significantly influence teacher work motivation and mediate the impact of transformational leadership on that motivation. Professional growth emerged as the factor contributing most significantly to teacher work motivation. These findings underscore that strengthening transformational leadership—supported by the continuous development of a growth mindset and professional growth—can serve as a vital strategy for enhancing teacher work motivation, especially in secondary schools located in non-urban areas.